2012
DOI: 10.1245/s10434-012-2799-z
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Diffusion-Weighted Imaging Over Positron Emission Tomography-Computed Tomography in Assessment of Hilar and Mediastinal Lymph Node in Lung Cancer

Abstract: DWI has advantages over PET-CT in diagnosing malignant from benign lymph nodes of lung cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…5 Although MRI has proven to be an invaluable tool for distinguishing RLN and cervical lymph node metastasis, 2,15,16 functional imaging, such as DWI, has been shown to facilitate diagnosis of lymph node metastasis in other malignant diseases. [17][18][19][20] Here, we evaluated the utility of DWI in differentiating metastatic from benign RLN in NPC, compared the accuracy of size-and ADC-based criteria in RLN metastasis and determined whether DWI would at all improve the diagnostic accuracy of RLN metastasis.…”
Section: Diagnosis Of Rln Metastasis With Dwimentioning
confidence: 99%
“…5 Although MRI has proven to be an invaluable tool for distinguishing RLN and cervical lymph node metastasis, 2,15,16 functional imaging, such as DWI, has been shown to facilitate diagnosis of lymph node metastasis in other malignant diseases. [17][18][19][20] Here, we evaluated the utility of DWI in differentiating metastatic from benign RLN in NPC, compared the accuracy of size-and ADC-based criteria in RLN metastasis and determined whether DWI would at all improve the diagnostic accuracy of RLN metastasis.…”
Section: Diagnosis Of Rln Metastasis With Dwimentioning
confidence: 99%
“…First, the sensitivity and accuracy of hilar and mediastinal lymph nodes by DWI were significantly higher than those of FDG-PET/CT. 28,29) Nomori et al 28) reported that the accuracy (89%) of DWI was significantly higher than that (78%) of FDG-PET/CT in 88 lung cancer cases, due to the fact that there was less overstaging cases with DWI compared with FDG-PET/CT.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it has not been demonstrated that DWI MRI has the potential to augment diagnostic sensitivity compared to conventional MRI sequences in the identifi cation of lymph node metastases [ 51 ]. Improved diagnostic sensitivity of DWI compared to 18 F-FDG PET/CT was reported for lung [ 52 ] but not for breast cancer [ 51 ]. Sensitivity was comparable for the detection of malignant lesions with 94 % for 18 F-FDG PET/CT vs. 91 % for whole-body DWI, while specifi city was signifi cantly lower for DWI (79 %) than for [ 46 , 53 ].…”
Section: Whole-body Mrimentioning
confidence: 99%